Exogenous kisspeptin (kp-10) resumes cyclicity in postpartum anestrus mithun cows - KHAN, M H; PERUMAL, P; HAZARIKA, S B; EZUNG, E (The Indian Journal of Animal Sciences, 2019)
Present study was conducted to assess the effect of exogenous kisspeptin administration on estrus induction, Kiss1gene expression, endocrinological profiles and follicular development in post partum (PP) anestrus mithun cows. Animals who failed to resume cyclicity after day 90–100 of parturition were selected. Experimental cows were examined thoroughly through per-rectal as well as ultrasonograpic examination to confirm the anestrous status. PP anestrous healthy mithun cows (12), aged 5–6 years (body condition score: 5–6 of 10) were selected with uniform anestrus status and randomly divided into 2 groups namely treatment (Gr I) and control (Gr II), each group consist 6 cows. Anestrus cows in Gr 1 were injected with kisspeptin @ 1.30 μg per kg body weight at 3 day interval for 21 days after 90–100 days of post parturition whereas in control group, normal saline was injected as placebo. Blood samples were collected on the days of injection and at estrus in both the groups. Trans-rectal ultrasonography was done at 3 days interval till onset of estrus and ovulation to study the follicular development. Exogenous kisspeptin administration caused significantly early resumption of cyclicity in treatment as compared to control (24.64±10.43 vs 66.56±14.66 days) and significantly increased kiss1 and GPR54 mRNA expression in treatment as compared to control on the day of estrus (1.943±0.29 vs 0.424±0.062 and 1.84±0.31 vs 0.416±0.082, respectively). Similarly, circulating level of estradiol and follicle stimulating hormone (FSH) increased gradually after exogenous administration of kisspeptin, which reached peak on the day of estrus in treatment group (25.36±1.27 pg/ml and 15.65±1.22 ng/ml, respectively) whereas no significant difference was observed between days of treatment in control group except on the day of estrus (11.29±1.76 pg/ml and 9.86±1.06 ng/ml, respectively). Level of estradiol and FSH on the day of estrus was significantly higher in treatment as compared to control whereas non-significant difference was observed in plasma progesterone concentration. Number of medium and large follicles increased in treatment whereas only small follicles were observed in control group. Improved endocrinological profiles, follicle development and kiss gene profiles in post partum anestrous mithun cows following exogenous kisspeptin indicates that kisspeptin inducted or resumed the cyclicity in early.